2017
DOI: 10.1016/j.chempr.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Anomalously Long-Lasting Blue PhOLED Featuring Phenyl-Pyrimidine Cyclometalated Iridium Emitter

Abstract: Blue phosphorescent material with both high efficiency and long durability is a long-standing challenge in the field of organic light-emitting devices (OLEDs). This work describes an anomalously blue phosphorescent OLED featuring the phenylpyrimidine cyclometalated iridium emitter, which has nearly unitary emission quantum yield, strong horizontal emitting dipole orientation, and short excitedstate lifetime to ensure high electroluminescence efficiency and a long device operation lifetime of T 50 > 2,200 hr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 88 publications
(122 reference statements)
0
66
0
Order By: Relevance
“…Phosphorescent iridium(III) complexes have been extensively used in numerousa pplications,s uch as bioimaging, [1][2][3][4][5] photoredox catalysis, [6][7][8] and sensing. [9,10] The most prolifica nd commerciallyf ruitful application has been in optoelectronic technology,i ncludingorganic light-emitting diodes( OLEDs) [11][12][13][14] and light-emitting electrochemical cells. [15,16] Their chief attributes that lend them to OLED applicationsi nclude chemical inertness, good thermal and photostability,a nd mosti mportantly their photophysicalp roperties, namely facile color tunability,h igh photoluminescence quantum yields (F PL ), and relatively short phosphorescence lifetimes (t).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorescent iridium(III) complexes have been extensively used in numerousa pplications,s uch as bioimaging, [1][2][3][4][5] photoredox catalysis, [6][7][8] and sensing. [9,10] The most prolifica nd commerciallyf ruitful application has been in optoelectronic technology,i ncludingorganic light-emitting diodes( OLEDs) [11][12][13][14] and light-emitting electrochemical cells. [15,16] Their chief attributes that lend them to OLED applicationsi nclude chemical inertness, good thermal and photostability,a nd mosti mportantly their photophysicalp roperties, namely facile color tunability,h igh photoluminescence quantum yields (F PL ), and relatively short phosphorescence lifetimes (t).…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of achieving high device efficiency and lifetime in blue OLEDs, in a very recent development, we carried out a comprehensive study on blue phosphorescent Ir(III) complexes consisting of difluorophenyl-pyrimidine (dfppm) as the cyclometalating ligand and picolinate or CF 3 -substituted pyridine-azoles as ancillary ligands and made a comparison with the benchmark blue emitter FIrpic. [15] This study has shown that by merely substituting the dfppy cyclometalating ligand in FIrpic yielded the compound MS 2, which exhibited a slightly bathochromic emission. However, switching the picolinatebased ancillary ligand to strong-field CF 3 -containing pyridine-azole ancillary ligands resulted in compounds MS 17 and MS 19 (Scheme 4) which were found to offset this bathochromic shift thereby leading to hypsochromic emission (versus FIrpic).…”
Section: Phosphorescent Iridium Complexesmentioning
confidence: 89%
“…[9] But, our group recently developed pyrimidine-based iridium complex with both high efficiency and long durability, and thus, circumvented the long-standing challenge of low device lifetimes in blue phosphorescent emitters. [15] This result may keep the momentum for searching new blue phosphors with reliable features to fulfill the demands of device efficiency and durability. Optimistically, the emergence of TADF emitters may provide a new way for solving this "blue problem".…”
Section: Introductionmentioning
confidence: 99%
“…A collaboration work of Wu, Chou, and Wong in Taiwan revealed that this sky-blue emitter showed an impressively high EQE and long-term device stability. 41 Surprisingly, an optimized sky-blue OLED exhibited a high EQE of 25% with Commission Internationale de l'Eclairage chromaticity coordinates (CIE) of (0.16, 0.38) and very long operation lifetime at 50% at the initial luminance of 327 cd m −2 (LT 50 , L 0 ¼ 327 cd m −2 ) of over 2200 h. This value is nearly 1000 times greater than that for the FIrpic. This representative result highlights pyrimidine-based organic semiconductors as promising and stable materials under electrical operation.…”
Section: Pyrimidine-containing Phosphorescent Emitters Based On Iridiummentioning
confidence: 90%
“…40 In this series of ligands, long-term stability in blue OLEDs remains a big challenge, and replacement of pyridine with pyrimidine unexpectedly provides great improvements of stability in blue OLEDs. 41 A pyrimidine-containing sky-blue phosphorescent emitter, iridium(III)bis(2-(2,4-difluorophenyl)-pyrimidine-N, C 2 0 )(picolinate) ½ðDFPPMÞ 2 IrðpicÞ, was originally developed by Ge et al 42 ðDFPPMÞ 2 IrðpicÞ showed an emission peak at 476 nm and had a shoulder peak at 496 nm in the CH 2 Cl 2 solution. The emission peak of ðDFPPMÞ 2 IrðpicÞ is 6 nm red-shifted compared with that of the pyridine-based FIrpic.…”
Section: Pyrimidine-containing Phosphorescent Emitters Based On Iridiummentioning
confidence: 99%